Analysis on Inference of Sound-to-Patterns in Multi-Lingual Context for Linguistic Reconstruction - Shilpa G V , Shashi Kumar D R, (International Journal of Advanced Science and Technology, 2020)
Finding the patterns in the sound plays a huge role in the linguistic reconstruction. They use it to prove the relationship between the languages and to recreate the proto forms based on shared developments. Cognate word is a word which means or looks alike in two different languages for example consider the word doctor in English then it means ‘däktər’ the French language these similarities between the two languages is known as the cognate words. Finding such similarities or the sound inference similarity between the cognate word helps to find the meaning of different words in different languages.